Implementing Punishment In Building Characters of Students at Pondok Pesantren DDI Mangkoso - Burga, Muhammad Alqadri (Badan Litbang dan Diklat Kementerian Agama RI, 2019)
AbstractThis research discusses implying punishment by teachers as an effort of character building for students such as honesty, discipline, and responsibility at Pondok Pesantren DDI Mangkoso with three focus problems, namely: 1) the form of the implementation of punishment in building characters of students; 2) the variety of obstacles to the implementation of punishment in building characters of the students and their solutions, and 3) the results of the implementation of punishment in building characters of students. This research was qualitative research by using pedagogy, psychology, juridical, and theological normative approaches. Sources of data have consisted of various level ages of respondents at the pesantren such as chairman, teachers, students, and students’ parents. Data were collected through observation, interviews, and documentation. Result of this research shows that forms of punishment consist of admonition, assigning assignments, psychic, and physical chastisement. Obstacles in applying the punishment are Child Protection Acts, environmental problems, and teacher’s creativities. Furthermore, a physical chastisement will be more optimum in students’ character building if it is supported collaboration between teachers and student’s parents.Abstrak Penelitian ini menganalisis penerapan hukuman oleh guru sebagai upaya pembinaan karakter jujur, disiplin, dan tanggung jawab santri pada Pondok Pesantren DDI Mangkoso, dengan tiga fokus masalah, yaitu: 1) bentuk penerapan hukuman dalam pembinaan karakter santri; 2) ragam hambatan penerapan hukuman dalam pembinaan karakter santri beserta solusinya, dan 3) hasil penerapan hukuman dalam pembinaan karakter santri. Jenis penelitian ini adalah kualitatif dengan pendekatan pedagogik, psikologis, yuridis, dan normatif teologis. Sumber data terdiri atas informan-informan dari berbagai unsur Pondok Pesantren DDI Mangkoso, yaitu: pimpinan, guru, santri, dan orang tua santri. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa bentuk hukuman yang diterapkan adalah teguran, pemberian tugas, hukuman psikis, dan hukuman fisik; hambatan-hambatannya adalah Undang-undang Perlindungan Anak, problem lingkungan, dan kreativitas guru; dan hukuman fisik lebih optimal dalam pembinaan karakter santri bila didukung oleh kerja sama yang baik dengan orang tua santri.